Protein profile, amino acids and taurine composition of sea slug (Paromoionchis tumidus) from Sumenep sea waters, Madura, Indonesia - Hafiludin Hafiludin; SRI ANDAYANI; HARTATI KARTIKANINGSIH; MUHAMAD FIRDAUS (Society for Indonesian Biodiversity, 2020)
Abstract. Hafiludin, Andayani S, Kartikaningsih H, Firdaus M. 2020. Protein profile, amino acids, and taurine composition of sea slug (Paromoionchis tumidus) from Sumenep sea waters, Madura, Indonesia. Biodiversitas 21: 2430-2436. Sea slug (Paromoionchis tumidus) is one of the marine gastropods and inhabits the intertidal zone. Sea slug has long been used by coastal communities as food and medicine for breast cancer. Sea slugs are rich in nutritional content, a protein with the composition of essential amino acids, unsaturated fatty acids, and minerals, which are important as food and medicine in the future. The objective of the study was to investigate the composition of proximate and amino acids, protein profile, and taurine content of sea slug from the sea waters of Sumenep Madura. In this work, the sea slug collected from Sumenep was analyzed for protein, amino acids, and taurine. We compared the composition of proximate and amino acids before and after dried (fresh and dried), and part of the body of a sea slug (whole, muscle, viscera, and mucus) for the protein profiling and taurine content. The results showed that protein content reached 9.32% (fresh) or 60.82% (dried). The molecular weight of the protein was ranging from 22.53 kDa (viscera) to 49.61 kDa (viscera). The total amino acids were found at 6.14% (fresh) and 53.87% (dried). Furthermore, taurine was present at range from 53.568 µg/mL (viscera) to 158.784 µg/mL (whole). This experiment imparted a consistent result with previous studies regarding the richness of protein content in sea slug. Thus there is a wide opportunity for using it as taurine rich products in functional food and medicine.